Nemesis - Reichs, Brendan (New York, NY : G.P. Putnam's Sons, 2017)
As the Anvil, an enormous asteroid, threatens to end all life on Earth, sixteen-year-old Min begins to uncover a lifetime of lies, a sinister conspiracy involving all students in her sophomore class in Fire Lake, Idaho.
Keywords: Asteroids -- Collisions with Earth -- Fiction; Survival -- Fiction; Conspiracies -- Fiction; Science fiction